A Major Earthquake and Tsunami in the Gulf of Cadiz in the Sixth Century B.C.? A Review of the Historical, Archaeological, and Geological Evidence. - Álvarez-Martí-Aguilar, Manuel (Seismological Society of America, 2023)
This article offers an overview of the published evidence of the possible occurrence of an earthquake and tsunami that, if factual, would have struck the shores of the Gulf of Cadiz sometime in the sixth century B.C. It addresses the oldest literary sources containing accounts of earthquakes and tsunamis in the Iberian peninsula, and their inclusion in the most important seismic catalogs in Spain and Portugal, as well as examining the geoarchaeological evidence of an earthquake and tsunami in the city of Huelva, dating to the first quarter of the sixth century B.C., relating it to geomorphological and sedimentary evidence of extreme wave events in the Gulf of Cadiz in about 2500 B.P. The information provided by Greek authors writing in the fifth and fourth centuries B.C., which depicts the ocean beyond the Strait of Gibraltar as impassable and replete with shallows, might also be an indirect reference to that seismic and high-energy marine event, whose intensity, exact date, and repercussions for the inhabitants of the Gulf of Cadiz are essential objects of research.
Keywords: Maremotos - Cádiz (Golfo) - S. VI A.C.; Geofísica en arqueología; Terremotos - Cádiz - S. VI A.C.; Tsunami; Tarteso; Terremoto; Catástrofes naturales